Analysis Role and Contribution of The Agricultural Sector in Sukoharjo District - Wahyu Adhi Saputro; Ramadhani A Sunaryono (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2020)
Sukoharjo Regency is one of the buffer districts in Central Java apart from Klaten Regency. Sukoharjo Regency has a potential agricultural sector, so this sector is the region's mainstay. This study aims to identify the role of the agricultural sector in economic development by analyzing the agricultural sector's performance (basis/not) and knowing the agricultural sector's contribution to the Gross Regional domestic product. The data used in this research is time series data from 2013-2017, sourced from the Central Statistics Agency of Sukoharjo Regency. The data analysis method used in this research is Location Quotient and Contribution. Based on the results of the study, it was found that the agricultural sector in Sukoharjo district was a basic sector, while the agricultural sector's contribution to the total Gross Regional Domestic Product was the highest in 2013, with a contribution of 9.86%. Keywords: Sukoharjo, LQ, Contribution, GDPJEL Classification: O40, R10, Q00